(untitled) (Journal of Accessibility and Design for All, 2018)
Out of 121 million population, 2.86 crore accounts for disabled people which 1.21% of total population. It has been reported that oral health care status of disabled people are poor than normal population. The main reason for this situation is barrier to access health care centres. This article throws light on definition and types of disability listed by Indian government. It also highlights the prevalence of disability and their oral health status. Article focuses on barrier in accessing dental care and guidelines required to build a disable friendly dental health care deliver center to make the treatment acceptable for such pupils. It is utmost important to provide dental care to such patients by overcoming the barrier to accessibility. Before motivating the patients and caregivers, it is the dentist who has to be motivated first in fulfilling special health care needs of patients resulting in improvement of quality of life.